Understanding the Relationship Between Child Marriage and Female Genital Mutilation - United Nations Children's Fund (United Nations, 2021)
The harmful practices of child marriage and Female Genital Mutilation (FGM) threaten the well-being of millions of girls around the world. In many countries where both practices are common, girls most at risk tend to share certain characteristics, including a low level of education, a rural residence, and a poorer household. Yet distinct drivers are also found, and in many communities where one practice is common, the other is not. This publication thus seeks to identify the extent to which child marriage and FGM co-exist. It presents an overview for all countries in which both practices have been documented, followed by an in-depth analysis for nine countries (Burkina Faso, Chad, Ethiopia, Guinea, Kenya, Mali, Senegal, Sierra Leone and Yemen). The intersection of these two practices – that is, the share of women who underwent FGM and were married in childhood – is reviewed over time to determine whether the likelihood of experiencing both has changed across generations. Characteristics that most frequently distinguish girls who experience one practice from those who experience both are also identified here.